Fitness and somatic conditioning of a sports level in a women`s volleyball team at the championship level - Rabka, A.; Rabka, P.; Klocek, T.; Spieszny, M. (Central European Journal of Sport Sciences and Medicine, 2015)
There is a significant complexity of movements and an ability to adapt to changing situations during a match, hence, a factor which decides about sports rank of a player is their motor fitness. The assessment of muscle power output and abilities of coordination in highrank players can be one of the most essential model indicators either in the process of athlete selection or in the process of sports training. The research question is: How the measured indicators of a somatic body construction and motor fitness condition the sports level of volleyball players who specialize in different tactical functions? The paper demonstrates the test results of 12 volleyball players from MKS Muszynianka - a vice-champion of Poland in 2009. Basic features of a somatic body construction were measured; the indicators of muscle dynamic strength, visual perception and visual-motor coordination were tested. The comparative analysis of the applied somatic and fitness indicators in the study explains both the model of choice of tactical specializations in the game and sports hierarchy of volleyball players at championship level. Lengthwise predispositions of a body construction are prominent in the model; however, fitness skills (muscle dynamic strength and visual-motor coordination) may well compensate for insufficient somatic indicators.